Linkages between primary seed dispersal, hydrochory and flood timing in a semi‐arid region river. (4th March 2013) - Kehr, Jacqueline M.; Merritt, David M.; Stromberg, Juliet C.; Turnbull, Lindsay
Abstract Questions Are seed release and hydrochory of riparian plants coupled with seasonal flood pulses for a river with bimodal flows? What phenological hydrochore guilds are present? How representative of riparian vegetation are hydrochores? What is the role of hydrochory in riparian plant community composition in arid land streams? Location Verde River, central Arizona, USA. Methods We recorded phenology of flowering and primary seed dispersal monthly for >100 riparian plant species, seined hydrochores 12 times during the growing season, sampled the extant plant community, and collected soil seed bank samples. Emergence of seedlings from hydrochore and soil samples was monitored for 1 yr in a greenhouse. Plant species were classified as to wetland indicator status and assessed for traits including life span, growth form and seed mass. Results Flowering and primary seed dispersal at the community level was bimodal for dryland species but more constant through time for wetland species. Numbers and richness of wetland hydrochores were high during the three floods that occurred in the atypical study year, while dryland species pulsed during a single flood. Three of 56 hydrochore taxa were vernal flood specialists, characterized by a spring hydrochore pulse during their period of seed release, and one was associated with summer floods. Another six were phenological generalists, with hydrochores constant or semi‐constant through time (including before and after primary dispersal) and persistent soil seed banks. Hydrochorous species spanned a wide range of traits, but overall had smaller seeds and higher wetland affinity than extant riparian vegetation. Conclusions As with other regions, hydrochory in dryland rivers is governed by the individual and combined influences of extrinsic factors, such as seasonal flow patterns and hydraulics, and intrinsic factors, such as timing of seed release and seed traits. Floods at different times during the season disperse distinct guilds, emphasizing the importance of flow variability for structuring riparian plant communities. Identifying temporal flood specialists and flood generalists is important, both for informing environmental flow regimes and for understanding patterns of plant distribution. The phenological dispersal plasticity of the generalist hydrochore species allows for adaptability to varying flow conditions and likely contributes to their broad geographic distributions.